Development of a Problem-Based Learning-Based Teaching Module on Sequences and Series to Enhance Students’ Mathematical Problem-Solving Abilities in Phase E - Fathimiyah Al Farra; Atma Murni; Syarifah Nur Siregar (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study aims to develop and test the feasibility of a Problem-Based Learning (PBL)-based Sequence and Series teaching module in facilitating the mathematical problem-solving abilities of Phase E students. This type of research is development research (Research and Development) that uses the ADDIE model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. In the analysis stage, observations and interviews were conducted with teachers and students at SMA Negeri 10 Pekanbaru to identify needs and problems in mathematics learning. The design stage focused on compiling a module based on PBL syntax, including problem orientation, student organization, investigation, development of work results, and evaluation and reflection. The developed module was validated by two Mathematics Education lecturers and one mathematics teacher to assess aspects of content, construction, language, and appearance. The validation results showed a validity level of 94% with a very valid category, while the practicality test results showed a value of 87% with a very practical category. Data collection techniques in this study included interviews, observations, questionnaires, and documentation. Data analysis related to validity and practicality was carried out using a percentage formula. These findings indicate that the developed teaching module is feasible and effective for mathematics instruction, particularly in improving students' problem-solving abilities. Therefore, this PBL-based teaching module can serve as an innovative learning tool that aligns with the principles of the Merdeka Curriculum and fosters students' critical, creative, and reflective thinking skills.